LGBTQI+ and Christian? Who decides?. Issue 4 (1st October 2020) - Harris, Helen; Yancey, Gaynor; Timbers, Veronica L.; Cole, Carolyn
ABSTRACT: Interviews with 20 adults who self-identified as both Christian and LGBTQI+ were examined for themes of identity and Christian history, affiliation, and vocation. Considered in the context of denominational and congregational struggles over scripture, policy, and decisions with respect to inclusion, leadership, and same sex marriage, these 20 participants have traditional histories and often non-traditional pathways to faith and service. The following manuscript will address these themes of identity and Christian history, affiliation, and vocation including the question of who determines who is a Christian and who is not.